1998
DOI: 10.1046/j.1365-2958.1998.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulations in lipid A and phospholipid biosynthesis pathways influence outer membrane protein assembly in Escherichia coli K‐12

Abstract: SummaryThe assembly defect of a mutant outer membrane protein, OmpF315, can be corrected by suppressor mutations that lower lipopolysaccharide (LPS) levels and indirectly elevate phospholipid levels. One such assembly suppressor mutation, asmB1, is an allele of lpxC (envA) whose product catalyses the first ratelimiting step in the lipid A (LPS) biosynthesis pathway. Besides reducing LPS levels, asmB1 confers sensitivity to MacConkey medium. A mutation, sabA1, that reverses the MacConkey sensitivity phenotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 33 publications
1
29
1
Order By: Relevance
“…Besides providing a means for colicins and filamentous phages to enter bacterial cells, the Tol-Pal system also has been suggested to maintain the integrity/stability of the outer membrane (24) and to participate in cell division by assisting in the invagination of the outer membrane during septum formation (23). Other cell envelope mutants with phenotypes resembling the eps phenotype arise from mutations in genes encoding one of the most abundant outer membrane proteins, Lpp (86,91), the Tat system (50, 84), or in genes coding for proteins involved in the biosynthesis of phospholipids and LPS (42).…”
Section: Discussionmentioning
confidence: 99%
“…Besides providing a means for colicins and filamentous phages to enter bacterial cells, the Tol-Pal system also has been suggested to maintain the integrity/stability of the outer membrane (24) and to participate in cell division by assisting in the invagination of the outer membrane during septum formation (23). Other cell envelope mutants with phenotypes resembling the eps phenotype arise from mutations in genes encoding one of the most abundant outer membrane proteins, Lpp (86,91), the Tat system (50, 84), or in genes coding for proteins involved in the biosynthesis of phospholipids and LPS (42).…”
Section: Discussionmentioning
confidence: 99%
“…The role of phospholipids in maintaining the integrity of the outer membrane has been demonstrated. Perturbation of outer-membrane biogenesis in E. coli by mutations which decrease lipid A synthesis (Karow et al, 1992) and suppress outer-membrane protein assembly (Kloser et al, 1998) results in elevated levels of phospholipid synthesis and incorporation into the outer membrane. Since both LPS and phospholipid pathways share common fatty acid precursors, this effect may be mediated by the shift in the flow of these precursors from one pathway to the other.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing a severely defective assembly mutant, OmpF315, suppressor mutations conferring a Dex ϩ phenotype were isolated. Further examination revealed that all the suppressor mutations mapped outside the ompF gene (11,12,15,17). A factor contributing to our inability to isolate intragenic suppressor mutations could have been the availability of a large number of potential chromosomal targets other than ompF that can be mutated to yield a Dex ϩ phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Naturally, compositional changes in any of these three compartments can potentially influence the biogenesis of OMPs. Accordingly, inner membrane components influence protein translocation (for a review, see reference 21), periplasmic components influence the early stages of OMP assembly (2,14,19,23), and outer membrane components such as lipopolysaccharide (LPS) can affect the later stages of OMP assembly (6,8,11,12,13,22,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation